Modelling linewidths of Kepler red giants in NGC 6819. Issue 1 (30th May 2018) - Aarslev, Magnus J; Houdek, Günter; Handberg, Rasmus; Christensen-Dalsgaard, Jørgen
Abstract: We present a comparison between theoretical, frequency-dependent, damping rates and linewidths of radial-mode oscillations in red giant stars located in the open cluster NGC 6819. The calculations adopt a time-dependent non-local convection model, with the turbulent pressure profile being calibrated to results of 3D hydrodynamical simulations of stellar atmospheres. The linewidths are obtained from extensive peakbagging of Kepler light curves. These observational results are of unprecedented quality owing to the long continuous observations by Kepler . The uniqueness of the Kepler mission also means that, for asteroseismic properties, this is the best data that will be available for a long time to come. We therefore take great care in modelling nine RGB stars in NGC 6819 using information from 3D simulations to obtain realistic temperature stratifications and calibrated turbulent pressure profiles. Our modelled damping rates reproduce well the Kepler observations, including the characteristic depression in the linewidths around the frequency of maximum oscillation power. Furthermore, we thoroughly test the sensitivity of the calculated damping rates to changes in the parameters of the non-local convection model.